2015
DOI: 10.1590/s1984-29612015074
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and external parasites of Enicognathus ferrugineus and Enicognathus leptorhynchus (Aves, Psittacidae) in Chile

Abstract: Parasite species are important components of biodiversity, as they provide valuable information about host health, evolutionary relationships, population structures, trophic interactions, the existence of environmental stresses, and climatic conditions. With the aim of describing the parasites associated with parrots of the genus Enicognathus Gray 1840 from central Chile, thirteen austral parakeets, Enicognathus ferrugineus, and five slender-billed parakeets, E. leptorhynchus, were examined between September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…These authors also reported that capillariosis is the main parasitic disease that affects these birds in captivity in Brazil and that it can be fatal to toucans. However, the Capillaria species found in the to psittacids (Kajerová and Baruš, 2005), being reported from different countries and continents (Weekes, 1982;Valdebenito et al, 2015). Cubas et al (2014) reported that Capillaria columbae Rudolphi, 1819 and Capillaria obsignata Madsen, 1945 being controlled with hygiene measures similar to those already mentioned for other parasites, and administration of anticoccidial drugs (Taylor et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…These authors also reported that capillariosis is the main parasitic disease that affects these birds in captivity in Brazil and that it can be fatal to toucans. However, the Capillaria species found in the to psittacids (Kajerová and Baruš, 2005), being reported from different countries and continents (Weekes, 1982;Valdebenito et al, 2015). Cubas et al (2014) reported that Capillaria columbae Rudolphi, 1819 and Capillaria obsignata Madsen, 1945 being controlled with hygiene measures similar to those already mentioned for other parasites, and administration of anticoccidial drugs (Taylor et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The two additional Protonyssus species were each described from a single host species: Protonyssus brevis (Trouessart, 1885) from Psittacula lunulata (=Bolbopsittacus lunulatus, Psittaculidae) from the Philippines, and Protonyssus proctorae Mironov et al 2005, from the extinct Conuropsis carolinensis, from North America (Trouessart 1885(Trouessart , 1916Gaud 1980;Gaud and Atyeo 1981;Mironov et al 2005). An undetermined species was recently reported from the two species of Enicognathus, E. ferrugineus (Statius Müller, 1776) and E. leptorhynchus (King, 1831) in Chile (Valdebenito et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Although ectoparasites are generally highly species-specific, lice tend to be very mobile, with many accidental reports, e.g. in birds of prey (see discussion on Heteromenopon macrurum in Valdebenito et al, 2015). Therefore, it is interesting that these phylogenetically closely related icterid birds (subfamily Agelaiinae) (Remsen et al, 2016) did not share a higher number of ectoparasites.…”
Section: Shared Parasite Faunamentioning
confidence: 99%